Peningkatan Literasi Keuangan bagi Ibu Rumah Tangga Anggota PKK Desa Mijen Kecamatan Kebonagung Kabupaten Demak Jawa Tengah - Astohar Astohar; Dhian Andanarini Minar Savitri; Emi Wardati; Adhitya Yoga Prasetya; Sugiharti Sugiharti; Trisa Indri Yani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Financial literacy plays a vital role in enhancing family well-being, particularly in the management of household income and expenditures. As the primary managers of household finances, homemakers need to possess a sound understanding of prudent financial management. This educational program was designed to provide and enhance financial literacy for homemakers who are members of the PKK organization in Mijen Village, Kebonagung District, Demak Regency. The implementation methods included the delivery of financial literacy materials accompanied by relevant examples, interactive discussions and question-and-answer sessions, as well as the provision of financial strategy recommendations aimed at achieving household financial well-being. The results of the program indicate that the core materials can be categorized into financial literacy enhancement, effective financial management, and investment (saving). The majority of participants allocate approximately 70% to 80% of their income to routine expenditures, while the remaining portion is used for non-routine needs and investments or savings.